The genomic identification of colombian acinetobacter baumannii clinical isolates by rflp-pcr analysis of the 16s-23s rrna gene spacer region (2011)
Identificación genómica de aislamientos colombianos de Acinetobacter baumannii mediante RFLP-PCR de la región intergénica espaciadora de los genes 16S y 23S rRNAAbstractThe 16S-23S rRNA gene intergenic spacer (ITS) was analysed by RFLP in this study to identify A. baumannii from 139 isolates from four hospitals (identified as A, B, C and D). One hundred and twenty of these isolates (86.3%) belonged to the A. baumannii species; those identified as being A. baumannii were found to be polyclonal (19 clone groups) when determining the genetic relationships, 16 of them being found in hospital C. Hospitals A, B and D shared two clone groups isolated during different years. This study describes a rapid and easy method for genospecies identification of Acinetobacter baumannii. Keywords: Acinetobacter baumannii-Acinetobacter calcoaceticus complex; 16S-23S rRNA gene intergenic spacer (ITS); RFLP-PCR. ResumenCon el objeto de identificar la genomoespecie Acinetobacter baumannii, se estudiaron 189 aislamientos pertenecientes al Complejo Acinetobacter baumannii-Acinetobacter calcoaceticus provenientes de cuatro hospitales colombianos (denominados A,B,C,D) mediante el análisis por RFLP-PCR de la región intergénica espaciador (ITS) de los genes 16S y 23S rRNA. Se encontraron 120 aislamientos (86.3%) pertenecientes a la especie A. baumannii. La estructura de la población fue policlonal, con 19 grupos clonales, 16 de los cuales se hallaron en el hospital C. En los hospitales A,B y D se encontraron 2 grupos clonales aislados durante diferentes años. En este estudio se propone un método rápido y fácil para la identificación de Acinetobacter baumannii Palabras clave: Complejo Acinetobacter baumannii-Acinetobacter calcoaceticus;  Región intergénica espaciadora (ITS), RFLP-PCR.